Dammed ponds! A study of post-fire sediment and carbon dynamics in beaver ponds and their contributions to watershed resilience - Dunn, Sarah B., author; Rathburn, Sara, advisor; Wohl, Ellen, committee member; Morrison, Ryan, committee member (Colorado State University. Libraries, 2023)
Excess sediment generated by wildfires threatens stream water quality, riparian habitat, and infrastructure. Beavers construct dams that pool water and capture sediment. Beaver ponds may bolster watershed resilience by providing sediment and carbon storage following wildfire. I tested the hypotheses that (1) burned ponds store greater relative volumes of sediment compared to unburned ponds, (2) post-fire sedimentation rates exceed pre-fire and unburned rates, and (3) post-fire sediment stored in beaver ponds is coarser and has a higher abundance of organic carbon relative to pre-fire sediment. I surveyed 48 beaver ponds in the Colorado Rocky Mountains. Approximately half of the ponds are in areas that burned in 2020 wildfires, whereas the other half remain unburned. Sites also spanned a range of geomorphic, vegetation, and individual pond characteristics. I conducted sediment probe surveys and collected sediment cores to quantify pond sediment storage and characterize sediment composition. Stratigraphic units present in sediment cores were analyzed for grain size and total organic carbon (TOC). Results indicate that beaver ponds in the Rocky Mountains store high volumes of sediment (mean = 796 m3). Burned ponds contain statistically significantly more relative sediment storage and have higher sedimentation rates than unburned ponds. Beaver ponds recorded high post-fire sedimentation rates (median = 19.8 cm/yr). Moreover, post-fire sedimentation rates are an order of magnitude higher than pre-fire rates in ponds with both pre- and post-fire sediments. Total sediment volume, sedimentation rates, grain size, and TOC content did not vary significantly between burned and unburned ponds. Geomorphology, vegetation, and pond characteristics exert additional influences on pond sediment dynamics. Pond characteristics determine the sediment trapping efficiency of ponds. Larger ponds store greater volumes of sediment, as do off-channel and older ponds. Ponds abandoned by beaver store greater volumes of sediment than actively maintained or human- constructed dams. Beaver activity and dam maintenance is critical for maintaining storage availability in ponds. Additionally, sedimentation rates are higher in ponds that are on-channel and recently constructed compared to off-channel and older ponds. These findings indicate that beaver-based restoration can be implemented prior to fire to provide critical post-fire sediment storage, thus enhancing watershed resilience and recovery.
Keywords: carbon; resilience; wildfire; pond; beaver; sediment